PENGARUH PENDEKATAN KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS DAN MOTIVASI BELAJAR SISWA PADA MATERI PENGOLAHAN DATA - Aisyah, Mamay Rahayu; Irawati, Riana; Sunarya, Dede Tatang (Jurnal Pena Ilmiah, 2019)
This research was taken because of the mistake of understanding the data processing concept, and lack of learning motivation in elementary students. Most of students immediately given questions in the form of data, students are not taught how to get a way where the data came from. The steps that are suitable to improve the ability of mathematical understanding and learning motivation of students on data processing material by using the Cooperative Type Two Stay Two Stray approach. Two Stay Two Stray is one type of learning from a cooperative approach. The purpose of the research conducted was to see the effect of using the Cooperative Two Stay Two Stray approach to the ability of mathematical understanding and student motivation in data processing material. This research used a quasi-experimental method using Nonequivalent Control Group Design. The population is all fourth grade elementary school students in Ujungjaya District, Sumedang Regency. While the sample was fourth grade students at SDN Cibuluh and fourth grade students at SDN Trijaya. The instrument used was a test of the learning outcomes of mathematical understanding, the scale of learning motivation, the observation format of teacher performance, and the observation format of student activities. The results of the research with a significance level = 0,05, showed that the Cooperative Two Stay Two Stray approach was better at improving studentsâ€™ mathematical comprehension and learning motivation in the data processing material than learning that has been done in the control class using conventional learning.Keywords: Cooperative Type Two Stay Two Stray, understanding and motivation.Â